Analisis Quantity Take-Off Pile Cap dan Tie Beam Berdasarkan Gambar Kerja Proyek Sekolah X - Afriyani Siburian; Ival Ardyansyah Gultom; Muhammad Rafa Rizqi Lubis; Thya Ifhada Tambunan; Edo Barlian; Melvi Maulita Napitupulu; Arrisha Anggraini (JURNAL TECNOSCIENZA, 2026)
Quantity estimation is one of the important stages in construction project planning because it affects material requirements and project execution in the field. One method commonly used to determine work quantities is Quantity Take-Off (QTO), which is carried out based on project construction drawings. This study aims to analyze the Quantity Take-Off results for pile cap and tie beam works based on the construction drawings of School X Project in Medan City. A descriptive quantitative method was employed using structural drawings and reinforcement details as the primary data sources. The research stages included structural element identification, calculation of concrete volume, reinforcement requirements, and formwork area for each element under review. The results showed that the total concrete requirement for pile cap and tie beam works was 258.096 m³, the reinforcement requirement was 24,735.317 kg, and the formwork requirement was 1,009.117 m². These findings indicate that accurate quantity estimation is essential to ensure proper material planning and to minimize the risk of material shortages or excesses during project execution. The results of this study can be used as a basis for material planning and quantity control, thereby supporting a more effective and well-organized construction process. In addition, this study may serve as a reference for the implementation of Quantity Take-Off in substructure works with similar characteristics.